Periocular Capillary Hemangioma Treated With Low Dose Oral Propranolol - Presentation and Outcome of 2 patients: Poster Presentation - Case Report - Ophthalmologist - TEGUH ANAMANI; PRIMA SUGESTY NURLAILA (Majalah Oftalmologi Indonesia, 2023)
Introduction : Infantile hemangioma (IH) is the most common benign vascular tumor of infancy. IH arises in the first few weeks of life, then displays a period of active growth followed by spontaneous involution.[1,2] Most IHs are uncomplicated, do not require intervention, and regress spontaneously.[3] Infantile hemangioma (IH) having an incidence of 4%–5%.[4-6] Case Illustration : First patient is 6 -month-old girl weighing 6.2 kg, with Periocular lesions on the superior palpebra since 2 weeks after birth. Second patient is 6-month-old girl weighing 6.3 kg, with Periocular lesions on the superior palpebra since 1 weeks after birth. The lesions rapidly increased in size within 1 months. The lesions made it difficult to open superior palpebra. Both patient was diagnosed with periocular infantile hemangioma. The diagnosis was established by clinical examination, and was given oral propranolol therapy. Initially, a dose of propranolol was 1 mg/kg body weight in divided doses for 2 weeks then increased to 2 mg/kg body weight. Patients have followed up at 4-week intervals until the final follow-up was reached according to the response of treatment. The lesions were significantly decreased and bith pastients could open their right eye normally after 3 months of propranolol therapy Discussion : Some cases of IH require early treatment. Early treatment is indicated for IH causing functional impairment. The use of propranolol in the management of IH is very effective in the reduction of the lesions and Has minimal side effects. Conclusion : Early diagnosis and intervention with propranolol for IH play an important role in determining the optimal outcomes